Corrosion-resistant PE protective film and application thereof

By designing a multi-layer structure in the PE protective film and using the combination of different components, its corrosion resistance in the acid-base corrosion process and its tensile properties in the sheet stretching stamping are improved, and the shortcomings of the existing PE protective film under these conditions are solved.

CN119636205APending Publication Date: 2025-03-18WUXI SANLI PROTECTIVE FILM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411815711.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing PE protective films are insufficient in corrosion resistance when facing acid-base corrosion processes, and are prone to rupture during the stretching and stamping of the sheet.

Method used

A corrosion-resistant PE protective film consisting of an outer layer, an intermediate layer and a corrosion-resistant layer is used. The outer layer and the intermediate layer are composed of different proportions of low-density polyethylene, metallocene linear low-density polyethylene and SEBS. The corrosion-resistant layer contains components such as acrylic resin, Wanhua emulsion, basalt fiber powder, etc.

Benefits of technology

The corrosion-resistant PE protective film shows extremely strong acid-base resistance in the acid-base corrosion process, and maintains good tensile properties during the sheet stretching and stamping process, reducing the risk of film rupture.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a corrosion-resistant PE protective film and application thereof. The corrosion-resistant PE protective film comprises an outer layer, a middle layer and a corrosion-resistant layer which are sequentially arranged from top to bottom, wherein the corrosion-resistant film layer comprises the following components in parts by weight; comprising the following components in parts by weight: 36-55 parts of low-density polyethylene, 20-30 parts of acrylic resin, 7-10 parts of a Wanhua emulsion, 6-12 parts of basalt fiber powder, 3-5 parts of cellulose ether, 2-5 parts of titanium dioxide, 1-3 parts of methyl methacrylate-butadiene-styrene, 1-3 parts of sodium carboxymethyl cellulose, 1-3 parts of an ethylene-acrylate-glycidyl methacrylate terpolymer and 1-3 parts of an antioxidant 1010. The corrosion-resistant PE protective film provided by the invention has extremely strong acid and alkali resistance, is subjected to acid and alkali corrosion process treatment protection, has very good stretchability, can be used as a plate for stretching and stamping, and is not easy to break.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a corrosion-resistant PE protective film and application thereof. Background Art

[0002] PE protective film is mainly used to protect products from pollution, corrosion, scratches during production, processing, transportation, storage and use, and to protect the original smooth and shiny surface, thereby improving product quality and market competitiveness. Due to the huge output of polyethylene and low cost, PE protective film can be seen on products in almost all walks of life.

[0003] The structure of PE protective film is generally divided into PE film layer and adhesive layer. The PE film layer has good hydrophobicity, waxy feel, non-stick surface, and also has the advantages of low temperature resistance, chemical corrosion resistance, and low water absorption. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant PE protective film and its application based on the above technical problems.

[0005] The technical solutions adopted are as follows:

[0006] A first aspect of the present invention provides a corrosion-resistant PE protective film, the corrosion-resistant PE protective film comprising an outer layer, an intermediate layer, and a corrosion-resistant layer arranged in sequence from top to bottom;

[0007] The outer layer comprises the following components by weight: 45-55 parts of metallocene linear low-density polyethylene, 10-12 parts of high-density polyethylene, and 10-15 parts of SEBS;

[0008] The intermediate layer comprises the following components by weight: 35-55 parts of low-density polyethylene, 20-30 parts of metallocene linear low-density polyethylene, 10-12 parts of SEBS, and 3-5 parts of ethylene-vinyl acetate copolymer;

[0009] The corrosion-resistant film layer comprises the following components in parts by weight:

[0010] 36-55 parts of low-density polyethylene, 20-30 parts of acrylic resin, 7-10 parts of Wanhua emulsion, 6-12 parts of basalt fiber powder, 3-5 parts of cellulose ether, 2-5 parts of titanium dioxide, 1-3 parts of methyl methacrylate-butadiene-styrene, sodium carboxymethyl cellulose, 1-3 parts of ethylene-acrylate-glycidyl methacrylate terpolymer, and 1-3 parts of antioxidant 1010.

[0011] Preferably, the thickness ratio of the outer layer, the intermediate layer and the corrosion-resistant layer is 2.1-4:2-2.5:1.

[0012] Further preferably, the melt flow rate of the metallocene linear low-density polyethylene is 1.0 to 3.5 g / 10 min, and the density is 0.860 to 0.920 g / cm 3 .

[0013] Preferably, the density of the high-density polyethylene is 0.94-0.95 g / cm 3 .

[0014] Preferably, the melt flow rate of the low-density polyethylene is 1.0 to 3.5 g / 10 min, and the density is 0.915 to 0.940 g / cm 3 .

[0015] More preferably, the average particle size of the basalt fiber powder is 10 to 50 μm.

[0016] Preferably, the viscosity of the sodium carboxymethyl cellulose is 900-1200 mpa·s.

[0017] According to a particularly preferred embodiment, the method for preparing the corrosion-resistant PE protective film comprises the following steps:

[0018] (1) Preparation of outer layer: weigh metallocene linear low-density polyethylene, high-density polyethylene, and SEBS according to the ratio, mix at 110-120° C. for 30-60 min, and cool naturally to room temperature;

[0019] (2) preparing the middle layer: weighing low-density polyethylene, metallocene linear low-density polyethylene, SEBS, and ethylene-vinyl acetate copolymer according to the ratio, mixing at 110-130° C. for 30-50 min, and naturally cooling to room temperature;

[0020] (3) Preparing a corrosion-resistant layer: Weighing Wanhua emulsion, basalt fiber powder, cellulose ether, titanium dioxide, and water according to a ratio, mixing them evenly to obtain a mixture I, and weighing low-density polyethylene, acrylic resin, and ethylene-acrylate-glycidyl methacrylate terpolymer according to a ratio, adding them to the mixture I, and mixing at 170-180° C. for 30-60 min, and then weighing methyl methacrylate-butadiene-styrene, sodium carboxymethyl cellulose, and antioxidant 1010 according to a ratio, mixing at 170-190° C. for 30-60 min, and cooling naturally;

[0021] (4) Extruding the outer layer, the middle layer and the corrosion-resistant layer in a twin-screw extruder, and baking at 100 to 120° C. for 90 to 120 minutes to obtain a corrosion-resistant PE protective film.

[0022] Preferably, in step (4), in the twin-screw extruder, the extrusion temperature is 150-180°C.

[0023] The second aspect of the present invention provides the application of the corrosion-resistant PE protective film described in the first aspect of the present invention in circuit board etching protection, range hood stamping protection, precision parts stamping protection, and electronic display glass etching.

[0024] The present invention has the following beneficial effects:

[0025] The corrosion-resistant PE protective film provided by the present invention has extremely strong acid and alkali resistance, can be protected by some acid and alkali corrosion process treatment, and has very good tensile properties, can be used as a plate for stretching and stamping, and is not easy to break. DETAILED DESCRIPTION

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] The corrosion-resistant PE protective film of the present invention and its application are described below in conjunction with specific embodiments.

[0028] In the following examples, unless otherwise specified, all raw materials used are commercially available.

[0029] In the following examples, unless otherwise specified, metallocene linear low-density polyethylene was purchased from Exxon Chemical Co., USA, with a brand name of 350D60;

[0030] Low-density polyethylene was purchased from LG Chemical Co., Ltd. of South Korea with a brand name of BF3000.

[0031] Example 1

[0032] A corrosion-resistant PE protective film, the PE protective film comprising an outer layer, an intermediate layer, and a corrosion-resistant film layer arranged in sequence from top to bottom;

[0033] The outer layer comprises the following components, by weight: 45 parts of metallocene linear low-density polyethylene, 11 parts of high-density polyethylene, and 15 parts of SEBS;

[0034] The intermediate layer comprises the following components, by weight: 55 parts of low-density polyethylene, 20 parts of metallocene linear low-density polyethylene, 10 parts of SEBS, and 5 parts of ethylene-vinyl acetate copolymer;

[0035] The corrosion-resistant film layer comprises the following components in parts by weight:

[0036] 55 parts of low-density polyethylene, 20 parts of acrylic resin, 7 parts of Wanhua emulsion, 6 parts of basalt fiber powder, 4 parts of cellulose ether, 5 parts of titanium dioxide, 1 part of methyl methacrylate-butadiene-styrene, sodium carboxymethyl cellulose, 2 parts of ethylene-acrylate-glycidyl methacrylate terpolymer, and 2.5 parts of antioxidant 1010.

[0037] The preparation method of the corrosion-resistant PE protective film comprises the following steps:

[0038] (1) Preparation of outer layer: Metallocene linear low-density polyethylene, high-density polyethylene and SEBS were weighed according to the ratio, mixed at 115° C. for 30 min, and naturally cooled to room temperature.

[0039] (2) Preparation of the middle layer: Low-density polyethylene, metallocene linear low-density polyethylene, SEBS, and ethylene-vinyl acetate copolymer were weighed according to the ratio, mixed at 120° C. for 40 min, and naturally cooled to room temperature.

[0040] (3) Preparation of corrosion-resistant layer: Wanhua emulsion, basalt fiber powder, cellulose ether, titanium dioxide, and water were weighed in proportion, mixed evenly, and a mixture I was obtained. Low-density polyethylene, acrylic resin, and ethylene-acrylate-glycidyl methacrylate terpolymer were weighed in proportion, added to the mixture I, and mixed at 175° C. for 30 min. Methyl methacrylate-butadiene-styrene, sodium carboxymethyl cellulose, and antioxidant 1010 were weighed in proportion, mixed at 180° C. for 50 min, and cooled naturally.

[0041] (4) Extruding the outer layer, the middle layer and the corrosion-resistant layer in a twin-screw extruder, and baking at 100° C. for 120 min to obtain a corrosion-resistant PE protective film; in the twin-screw extruder, the extrusion temperature of the outer layer is: 166° C. for barrel section 1, 170° C. for barrel section 2, and 175° C. for barrel section 3; the extrusion temperature of the middle layer is: 156° C. for barrel section 1, 170° C. for barrel section 2, and 180° C. for barrel section 3; the extrusion temperature of the corrosion-resistant layer is: 151° C. for barrel section 1, 155° C. for barrel section 2, and 165° C. for barrel section 3.

[0042] In the corrosion-resistant PE protective film, the thickness ratio of the outer layer, the middle layer and the corrosion-resistant layer is 3:2:1, and the thickness of the corrosion-resistant PE protective film is 65 μm.

[0043] Example 2

[0044] A corrosion-resistant PE protective film, the PE protective film comprising an outer layer, an intermediate layer, and a corrosion-resistant film layer arranged in sequence from top to bottom;

[0045] The outer layer comprises the following components, by weight: 55 parts of metallocene linear low-density polyethylene, 12 parts of high-density polyethylene, and 15 parts of SEBS;

[0046] The intermediate layer comprises the following components, by weight: 45 parts of low-density polyethylene, 30 parts of metallocene linear low-density polyethylene, 12 parts of SEBS, and 4 parts of ethylene-vinyl acetate copolymer;

[0047] The corrosion-resistant film layer comprises the following components in parts by weight:

[0048] 45 parts of low-density polyethylene, 30 parts of acrylic resin, 9 parts of Wanhua emulsion, 10 parts of basalt fiber powder, 5 parts of cellulose ether, 4 parts of titanium dioxide, 3 parts of methyl methacrylate-butadiene-styrene, sodium carboxymethyl cellulose, 2 parts of ethylene-acrylate-glycidyl methacrylate terpolymer, and 1 part of antioxidant 1010.

[0049] The preparation of the corrosion-resistant PE protective film is the same as in Example 1. In the corrosion-resistant PE protective film, the thickness ratio of the outer layer, the middle layer and the corrosion-resistant layer is 4:2.5:1, and the thickness of the corrosion-resistant PE protective film is 62 μm.

[0050] Example 3

[0051] A corrosion-resistant PE protective film, the PE protective film comprising an outer layer, an intermediate layer, and a corrosion-resistant film layer arranged in sequence from top to bottom;

[0052] The outer layer comprises the following components, by weight: 50 parts of metallocene linear low-density polyethylene, 10 parts of high-density polyethylene, and 10 parts of SEBS;

[0053] The intermediate layer comprises the following components, by weight: 35 parts of low-density polyethylene, 30 parts of metallocene linear low-density polyethylene, 12 parts of SEBS, and 3 parts of ethylene-vinyl acetate copolymer;

[0054] The corrosion-resistant film layer comprises the following components in parts by weight:

[0055] 36 parts of low-density polyethylene, 30 parts of acrylic resin, 7 parts of Wanhua emulsion, 10 parts of basalt fiber powder, 5 parts of cellulose ether, 3 parts of titanium dioxide, 2.5 parts of methyl methacrylate-butadiene-styrene, sodium carboxymethyl cellulose, 3 parts of ethylene-acrylate-glycidyl methacrylate terpolymer, and 3 parts of antioxidant 1010.

[0056] The preparation of the corrosion-resistant PE protective film is the same as in Example 1. In the corrosion-resistant PE protective film, the thickness ratio of the outer layer, the middle layer and the corrosion-resistant layer is 2.1:2:1, and the thickness of the corrosion-resistant PE protective film is 60 μm.

[0057] Test Case

[0058] The ultra-low viscosity electronic protective film emulsion pressure-sensitive adhesive prepared in the above examples and comparative examples was coated on the surface of the PE substrate, with a coating amount of 25 g / m 2 , and the obtained pressure-sensitive tape was tested, and the results are shown in Table 1.

[0059] Among them, the 180° peel strength is carried out according to GB / T 2791-1995 standard;

[0060] The aging test was conducted at a temperature of 85°C and a humidity of 85% for 7 days (24 hours);

[0061] The bonding strength test was carried out in accordance with GB / T 2792-2014 standard, selecting the 180° peel strength test method, carried out at 25°C, and tested after 10 days.

[0062] Table 1

[0063] Light transmittance / % 180° peel strength / (g / 25mm) Aging test Adhesion strength / (N / cm) Example 1 92 6.1 No ghosting, no residual glue 9.0 Example 2 91 5.5 No ghosting, no residual glue 8.9 Example 3 90 5.8 No ghosting, no residual glue 8.5

[0064] It can be seen from the above results that the corrosion-resistant PE protective film obtained by the present invention has significantly better corrosion resistance, peel strength, and lower viscosity.

[0065] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A corrosion-resistant PE protective film, characterized in that: The corrosion-resistant PE protective film comprises an outer layer, an intermediate layer and a corrosion-resistant layer arranged in sequence from top to bottom; The outer layer comprises the following components by weight: 45-55 parts of metallocene linear low-density polyethylene, 10-12 parts of high-density polyethylene, and 10-15 parts of SEBS; The intermediate layer comprises the following components by weight: 35-55 parts of low-density polyethylene, 20-30 parts of metallocene linear low-density polyethylene, 10-12 parts of SEBS, and 3-5 parts of ethylene-vinyl acetate copolymer; The corrosion-resistant film layer comprises the following components in parts by weight: 36-55 parts of low-density polyethylene, 20-30 parts of acrylic resin, 7-10 parts of Wanhua emulsion, 6-12 parts of basalt fiber powder, 3-5 parts of cellulose ether, 2-5 parts of titanium dioxide, 1-3 parts of methyl methacrylate-butadiene-styrene, sodium carboxymethyl cellulose, 1-3 parts of ethylene-acrylate-glycidyl methacrylate terpolymer, and 1-3 parts of antioxidant 1010.

2. The corrosion-resistant PE protective film according to claim 1, wherein: The thickness ratio of the outer layer, the intermediate layer and the corrosion-resistant layer is 2.1-4:2-2.5:

1.

3. The corrosion-resistant PE protective film according to claim 1 or 2, wherein: The metallocene linear low-density polyethylene has a melt flow rate of 1.0 to 3.5 g / 10 min and a density of 0.860 to 0.920 g / cm 3 .

4. The corrosion-resistant PE protective film according to claim 1 or 2, wherein: The density of the high-density polyethylene is 0.94-0.95 g / cm 3 .

5. The corrosion-resistant PE protective film according to claim 1 or 2, wherein: The melt flow rate of the low-density polyethylene is 1.0-3.5 g / 10 min, and the density is 0.915-0.940 g / cm 3 .

6. The corrosion-resistant PE protective film according to claim 5, wherein: The average particle size of the basalt fiber powder is 10 to 50 μm.

7. The corrosion-resistant PE protective film according to claim 5, wherein: The viscosity of the sodium carboxymethyl cellulose is 900-1200 mpa·s.

8. The corrosion-resistant PE protective film according to claim 1 or 2, wherein: The method for preparing the corrosion-resistant PE protective film comprises the following steps: (1) Preparation of outer layer: weigh metallocene linear low-density polyethylene, high-density polyethylene, and SEBS according to the ratio, mix at 110-120° C. for 30-60 min, and cool naturally to room temperature; (2) preparing the middle layer: weighing low-density polyethylene, metallocene linear low-density polyethylene, SEBS, and ethylene-vinyl acetate copolymer according to the ratio, mixing at 110-130° C. for 30-50 min, and naturally cooling to room temperature; (3) Preparing a corrosion-resistant layer: Weighing Wanhua emulsion, basalt fiber powder, cellulose ether, titanium dioxide, and water according to a ratio, mixing them evenly to obtain a mixture I, and weighing low-density polyethylene, acrylic resin, and ethylene-acrylate-glycidyl methacrylate terpolymer according to a ratio, adding them to the mixture I, and mixing at 170-180° C. for 30-60 min, and then weighing methyl methacrylate-butadiene-styrene, sodium carboxymethyl cellulose, and antioxidant 1010 according to a ratio, mixing at 170-190° C. for 30-60 min, and cooling naturally; (4) Extruding the outer layer, the middle layer and the corrosion-resistant layer in a twin-screw extruder, and baking at 100 to 120° C. for 90 to 120 minutes to obtain a corrosion-resistant PE protective film.

9. The corrosion-resistant PE protective film according to claim 8, wherein: In step (4), in the twin-screw extruder, the extrusion temperature is 150 to 180°C.

10. Application of the corrosion-resistant PE protective film according to any one of claims 1 to 9 in etching protection of circuit boards, stamping protection of range hoods, stamping protection of precision parts, and etching of glass for electronic display screens.